2007
DOI: 10.1111/j.0030-1299.2007.15461.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of food intake and ingesta passage predicts feeding ecology in two different megaherbivore groups

Abstract: Digestion, especially of plant material, is a time-dependent process. In herbivores, an increase in food intake is usually correlated to an acceleration of ingesta passage through the gut, and could hence depress digestive efficiency. Therefore, the nature of the relationship between food intake and ingesta passage (i.e. whether the increase in ingesta passage due to the increase in food intake is mild or drastic) should determine the flexibility of the feeding strategy of herbivore and omnivore species. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 70 publications
6
71
1
Order By: Relevance
“…Such a significant 392 negative correlation was only found for ruminants, but not for hindgut fermenters. In insensitivity of MRT to an increase in intake has been considered as a major trait in digestive 398 strategies of herbivores (Clauss et al, 2007b), as appears evident in the group of equids and 399 elephants in this study (Fig. 5).…”
Section: (Calculated With Romi) a Potential Important 371mentioning
confidence: 51%
“…Such a significant 392 negative correlation was only found for ruminants, but not for hindgut fermenters. In insensitivity of MRT to an increase in intake has been considered as a major trait in digestive 398 strategies of herbivores (Clauss et al, 2007b), as appears evident in the group of equids and 399 elephants in this study (Fig. 5).…”
Section: (Calculated With Romi) a Potential Important 371mentioning
confidence: 51%
“…For example, holding metabolic rates steady, the decreased surface areato-volume ratio of large body size permits a higher body temperature with lower energy expenditure (gigantothermy) [10]. Likewise, increased gut volume (or, by proxy, BM) maximizes digestibility of fibrous plant material through elongation of the gastrointestinal tract and longer gut retention times in living herbivores [1,3,11,12], despite potential reductions in gut surface area-to-volume ratio [8] and potential intake limits [13]. Given this relationship, one would expect increasing body size to pose a selective advantage during the evolution of herbivorous tetrapods, and such a pattern has indeed been speculated for a myriad of taxa, including Palaeozoic amniotes [14], extant lizards [4,15], Palaeogene and modern mammals [16,17], and non-avian dinosaurs [6,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated the negative correlation between DMI and MRT in ratites (Frei et al, 2015c), sloths (Vendl et al, 2015), ruminants (Clauss et al, 2007;Hammond et al, 2014) and macropods (Munn et al, 2008). In essence, a higher food intake leads to a faster passage of digesta through the digestive tract, mostly because of the limited capacity of the gut to expand.…”
Section: Effect Of Feeding Regimen and Kangaroo Species On Methane Emmentioning
confidence: 99%